President’s Message - Farley, Margaret (Operating Room Nurses Association of Canada Journal, 2004)
Last year, as I traveled on ORN AC business, I found that I was coming across the same topics no matter where I was. At the 18th National ORNAC Conference, the National Association of Theatre N urses (NATN) Annual Congress, the Operating Room Nurses Association of Alberta (ORNAA) conference or at meetings with the Saskatchewan OperatingRoomNursesGroup(SORNG)the topics and the themes were pretty consistent. Our world may be physically vast, but it seems we are all dealing with the same issues around the world.